General Economic and Social Problems in the Conditions of Innovation and Digital Economy - Yuldasheva, Ashurova Oltin (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article is about de digital economy and “Wat is the digital economy?”, on such important issues as “Problems and tasks of the digital economy”, “The impact of the digital economy in Uzbekistan”.